Social Interaction and Political Communication of Female Politician - Verlita Evelyn Raimond; Poppy Ruliana (Ikatan Sarjana Komunikasi Indonesia, 2022)
The public’s views about the position of women that have not contributed a lot to and have not been much engaged in politics, among others, pose a challenge to women to interact in the social environment as well as to communicate their ideas in politics. While men make up a majority of politicians in Indonesia, only a few women are politicians. The social interaction and political communication of female politicians become a topic that is worth studying. This research focuses on a female politician, Indah Kurnia, who sits in the House Representatives of the Republic of Indonesia (DPR RI). The conceptual and theoretical method used in this study is a theory in the communication science, particularly social interaction and political communication. This research uses qualitative method, particularly in conducting interviews with one primary informant and two additional informants. The result and discussion of this research show that the woman raised in this research is an individual that has a variety of social interactions in the diverse social environment. In addition, she also has typical characteristics of strategy for political communication media covering personal campaign, moderate, comprehensive and more-than–expected appearance, exemplary leadership and concrete work, and music.